Sobrevida e desfechos periimplantares de overdentures mandibulares retidas por quatro mini implantes de titânio-zircônia: ensaio clínico randomizado de um ano de acompanhamento - Curado, Thalita Fernandes Fleury (2023)
Mandibular overdenture is considered the standard treatment for completely edentulous patients, with excellent cost-effectiveness and high success rates. The traditional technique consists of installing two implants of conventional diameter, its use being limited in very resorbed ridges with reduced thickness. Mini-implants are small-diameter implants that have recently been used to retain overdentures with satisfactory success rates. The aim of this study is to evaluate the survival and peri-implant outcomes of a mini-implant system for overdenture retention and the influence of surgical and loading protocols performed. The present study consists of a 2x2 factorial randomized clinical trial where 74 total edentulous participants underwent the installation of four mini-implants for overdenture retention in the mandibular interforaminal region, totaling 296 mini-implants. They were randomized into four groups according to the surgical protocol and prosthesis loading: Immediate/Flapless = 17 (23.0%); Immediate/Flapped = 18 (24.3%); Delayed/Flapless = 20 (27.0%); and Delayed/Flapped = 19 (25.7%). Most participants (64.9%) were female and the mean age at surgery was 64.1 ± 8 years. The survival rate during the 1-year follow-up was 100%. No major biological complications were observed, such as abnormal marginal bone loss or sulcus depth. The plaque index remained stable at the follow-ups (3, 6 and 12 months after capture) while the bleeding index significantly reduced at the 6 and 12 months follow-ups compared to the baseline index (3 months). Probing depth and gingival margin height remained stable over the follow-up periods. The mean overall marginal bone loss was 0.68 (±0.68) mm after three months and 0.89 (±0.75) mm after one year. The flapless protocol showed better results in stability and soft tissue health and a slightly higher risk of marginal bone loss. The findings suggest that the mandibular overdenture retained by this new mini-implant system is a safe and predictable treatment option with regard to implant survival and peri-implant outcomes, even when flapless surgery and immediate loading are adopted.